The Value of Speech-Language Pathologists in Concussion Management - Ketcham, Caroline J.; Bowie, Melissa; Buckley, Thomas A.; Baker, Martin; Patel, Kirtida; Hall, Eric E. (Current Research: Concussion, 2017)
Objective The goal of this article is to make a case for the value of a speech-language pathologist (SLP) to be considered for inclusion on a concussion management team in a consultant capacity and resource for student-athletes during the return-to-learn process particularly at the high school or collegiate level where they may already be on staff or affiliated. SLPs have the skills and expertise to address difficulties and provide structured strategies to address symptoms of a concussion that affect cognitive processing, attention, and focus which often are impacted during recovery from a concussion. These skills alongside an athletic trainer/school nurse will provide a mechanism for student-athletes to be monitored and have a resource through the return-to-learn and return-to-play process.
Keywords: speech-language pathologists; SLP; concussion management